Oil dependency of the Russian economy: an econometric analysis - Andreas Benedictow; Daniel Fjærtoft; Ole Løfsnæs (Statistics Norway, Research Department, 2010)
A macro econometric model of the Russian economy is developed, containing 13 estimated equations - covering major national account variables, government expenditures and revenues, interest rates, prices and the labour market. The model is tailored to analyze effects of changes in the oil price and economic policy variables. The model has good statistical properties and tracks history well over the estimation period, which runs from 1995Q1 to 2008Q1. Model simulations indicate that the Russian economy is vulnerable to large fluctuations in the oil price, but we also find evidence of significant economic growth capabilities in the absence of oil price growth.
Keywords: C51; E17; E52; E63; Q43; 330; Russia; macro econometric model; oil price dependency; fiscal and monetary policy